The Acute Effects of Amyloid-Beta1–42 on Glutamatergic Receptor and Transporter Expression in the Mouse Hippocampus - Yeung, Jason H. Y.; Palpagama, Thulani H.; Tate, Warren P.; Peppercorn, Katie; Waldvogel, Henry J.; Faull, Richard L. M.; Kwakowsky, Andrea (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD) is the leading type of dementia worldwide. Despite an increasing burden of disease due to a rapidly aging population, there is still a lack of complete understanding of the precise pathological mechanisms which drive its progression. Glutamate is the main excitatory neurotransmitter in the brain and plays an essential role in the normal function and excitability of neuronal networks. While previous studies have shown alterations in the function of the glutamatergic system in AD, the underlying etiology of beta amyloid (Aβ1–42) induced changes has not been explored. Here we have investigated the acute effects of stereotaxic hippocampal Aβ1–42 injection on specific glutamatergic receptors and transporters in the mouse hippocampus, using immunohistochemistry and confocal microscopy 3 days after Aβ1–42 injection in aged male C57BL/6 mice, before the onset of neuronal cell death. We show that acute injection of Aβ1–42 is sufficient to induce cognitive deficits 3 days post-injection. We also report no significant changes in glutamate receptor subunits GluA1, GluA2, VGluT1, and VGluT2 in response to acute injection of Aβ1–42 when compared with the ACSF-vehicle injected mice. However, we observed increased expression in the DG hilus and ventral stratum (str.) granulosum, CA3 str. radiatum and str. oriens, and CA1 str. radiatum of the GluN1 subunit, and increased expression within the CA3 str. radiatum and decreased expression within the DG str. granulosum of the GluN2A subunit in Aβ1–42 injected mice compared to NC, and a similar trend observed when compared to ACSF-injected mice. We also observed alterations in expression patterns of glutamatergic receptor subunits and transporters within specific layers of hippocampal subregions in response to a microinjection stimulus. These findings indicate that the pathological alterations in the glutamatergic system observed in AD are likely to be partially a result of both acute and chronic exposure to Aβ1–42 and implies a much more complex circuit mechanism associated with glutamatergic dysfunction than simply glutamate-mediated excitotoxic neuronal death.